The limiting class of distributions cumulative sums for independent m-valued random variables - Mišeikis, F. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ф. Мишейкис. Класс предельных распределений для сумм m-значных независимых случайных величинF. Mišeikis. Nepriklausomų m-reikšmių atsitiktinių dydžių sumų ribinių pasiskirstymų klasė